Anaerobic Membrane Bioreactor (AnMBR) economic viability on swine operations - Parker, Emily (Kansas State University, 2021)
Waste management in agriculture provides an important opportunity to reduce greenhouse gas emissions, recover nutrients, recycle water, and improve water quality. The objective of this study is to provide the first analysis of the economic viability of new technology for waste management – the Anaerobic Membrane Bioreactor (AnMBR). The AnMBR system utilizes biological processes to transform manure into marketable products. Previous work has analyzed the economic viability in municipal wastewater settings, but I focus on the viability for hog operations. My analysis identifies which combination of nutrient recovery systems in conjunction with the AnMBR is the most viable and the effects of government subsidies or valuing the external benefits. I focus on a comparison of the AnMBR with anaerobic digesters that have been adopted for manure management by some livestock operations. The data used represents a pilot-scale AnMBR that was designed for research purposes. A full-scale system with the capacity to treat waste from 5,000 hogs was calculated to be approximately five times the size of the pilot-scale in terms of flow-rate. I utilize net present value (NPV) to measure the viability of both pilot and full-scale systems. Assuming a 20-year useful life, a 6% discount rate, compressed natural gas (CNG) end-use for the biogas, and the ability to trade renewable identification numbers (RINs), a positive NPV was not obtained for either pilot or full-scale configurations until social benefits were considered, and the greatest NPV scenario included the AnMBR system only – no additional nutrient recovery systems. Most importantly, the configuration with the AnMBR system only was preferred to the bioreactor tank only scenario. Thus, the AnMBR system is more beneficial than the complete mix anaerobic digesters already used on farms today since the bioreactor tank is equated to a complete mix anaerobic digester based on the potential private benefits. Finally, the subsidy scenario improved the NPV for all configurations.
Keywords: Economic feasibility; Anaerobic Membrane Bioreactor (AnMBR); Swine waste; Manure management; Nutrient recovery